Comparison between different markers for sperm quality in the cat: Diff-Quik as a simple optical technique to assess changes in the DNA of feline epididymal sperm - Mota, Paula C. (2006)
The majority of wild felids, as well as some domestic cats, have low sperm concentration in their ejaculates, and a high proportion of abnormal spermatozoa. We have employed several possible semen quality markers to further characterize cat epididymal sperm. Methods included possible apoptotic reporters, such as the annexin V assay to monitor exposure of phosphatidylserine (PS) on the outer leaflet of the plasma membrane, as well as cell integrity; and the TUNEL assay to quantify DNA breaks. Sperm surface ubiquitination, another putative marker of sperm quality, was also monitored. The annexin V assay revealed a high percentage of sperm with PS exposure, and the TUNEL assay pointed to high levels (13 ± 12%) of sperm with DNA breaks. Correlations were found between apoptotic markers (but not ubiquitination) and semen parameters. In parallel to this analysis, cat sperm morphology was evaluated using the Diff-Quik optical stain, which has been used in human reproduction laboratories. Several types of abnormalities could be characterized with this method. Remarkably, head staining abnormalities detected using the Diff-Quik staining method were strongly correlated with, and could accurately predict, sperm DNA defects detected in the same sample using the TUNEL assay. We therefore suggest that sperm morphology analysis using Diff-Quik could be used in field conditions to assess sperm status, due to the simplicity of the procedure and the equipment involved.